Development of Ethnomathematics Teaching Materials to The Character Education Student's of Junior High School - Nuryadi, Nuryadi; Fitriadhy, Ahmad; Hetty Marhaeni, Nafida (Technium Sustainability, 2022)
Education and culture play an important role in developing the noble values of a nation that have an impact on the formation of human character. However, the reality is that cultural values and character are increasingly eroding based on current phenomena. For this reason, it is necessary to have teaching materials that integrate character and cultural education to prevent this from being eroded. One that can bridge between culture and character-based education is ethnomathematics. For this reason, this study aims to develop teaching materials in the form of the friend app application to improve student character education through good quality puppet characters seen from the criteria of validity and practicality. This type of research is Research and Development (R&D) which refers to the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). This research was conducted in class VIII SMP Negeri 2 Godean. In addition to students, the source of data in this study is a validator. The instruments used were the KaWan app, material expert validation questionnaire, media expert validation questionnaire and student response questionnaires. The results showed that the validity aspect was categorized as very good from the material expert and media expert validator and the practicality aspect was categorized both for small-scale trials and large-scale trials. So, KaWan apps based on character education for wayang figures to improve character education are declared suitable for use. This research will still be continued to achieve the effective criteria.